Dysfunctional or hyperfunctional? The amygdala in posttraumatic stress disorder is the bull in the evolutionary China shop. Issue 6 (29th October 2015) - Diamond, David M.; Zoladz, Phillip R.
Abstract : Our motivation in writing this Review arose not only from the great value in contributing to this special issue of the Journal of Neuroscience Research but also from the desire to express our opinion that the description of the amygdala as "dysfunctional" in posttraumatic stress disorder (PTSD) might not be appropriate. We acknowledge that excessive activation of the amygdala contributes to the cluster of PTSD symptoms, including hypervigilance, intrusive memories, and impaired sleep, that underlies the devastating mental and physical outcomes in trauma victims. The issue that we address is whether the symptoms of PTSD represent an impaired (dysfunctional) or sensitized (hyperfunctional) amygdala status. We propose that the amygdala in PTSD is hyperfunctional rather than dysfunctional in recognition of the fact that the individual has already survived one life‐threatening attack and that another may be forthcoming. We therefore consider PTSD to be a state in which the amygdala is functioning optimally if the goal is to ensure a person's survival. The misery caused by a hyperfunctional amygdala in PTSD is the cost of inheriting an evolutionarily primitive mechanism that considers survival more important than the quality of one's life. © 2015 Wiley Periodicals, Inc.